# 6r^2+11r-10=0

## Simple and best practice solution for 6r^2+11r-10=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 6r^2+11r-10=0 equation:

Simplifying
6r2 + 11r + -10 = 0

Reorder the terms:
-10 + 11r + 6r2 = 0

Solving
-10 + 11r + 6r2 = 0

Solving for variable 'r'.

Factor a trinomial.
(-5 + -2r)(2 + -3r) = 0

Subproblem 1Set the factor '(-5 + -2r)' equal to zero and attempt to solve:

Simplifying
-5 + -2r = 0

Solving
-5 + -2r = 0

Move all terms containing r to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -2r = 0 + 5

Combine like terms: -5 + 5 = 0
0 + -2r = 0 + 5
-2r = 0 + 5

Combine like terms: 0 + 5 = 5
-2r = 5

Divide each side by '-2'.
r = -2.5

Simplifying
r = -2.5
Subproblem 2Set the factor '(2 + -3r)' equal to zero and attempt to solve:

Simplifying
2 + -3r = 0

Solving
2 + -3r = 0

Move all terms containing r to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + -3r = 0 + -2

Combine like terms: 2 + -2 = 0
0 + -3r = 0 + -2
-3r = 0 + -2

Combine like terms: 0 + -2 = -2
-3r = -2

Divide each side by '-3'.
r = 0.6666666667

Simplifying
r = 0.6666666667Solutionr = {-2.5, 0.6666666667}`